Jatropha gossypiifolia L. and its biologically active metabolites: A mini review - Wu, Qinghua; Patočka, Jiří; Nepovimova, Eugenie; Kuca, Kamil (Elsevier Ireland Ltd., 2019)
Ethnopharmacological relevance: Jatropha gossypiifolia L. (Euphorbiaceae) is popularly known as bellyache bush or black physic nut and is widely used in local / traditional medicine due to the various biological activities attributed to its different parts, including its leaves, roots, and latex. Aim of the study: In this review, we aim to update and discuss the chemistry, specific pharmacology, and toxicological activities of Jatropha gossypiifolia and its bioactive metabolites. Materials and methods: The Web of Science, PubMed, Google Scholar, SciFinder, Cochrane Library, Scopus, and Science Direct databases were searched with the name "Jatropha gossypiifolia" and the term "bioactive metabolites". All studies on the chemistry, pharmacology, and toxicology of the plant up to December 2018 were included in this review.
Keywords: Jatropha gossypiifolia; Bioactive metabolites; Pharmacology; Toxicology; Alternative medicine